2017
DOI: 10.1111/nph.14941
|View full text |Cite
|
Sign up to set email alerts
|

OsCERK1 plays a crucial role in the lipopolysaccharide‐induced immune response of rice

Abstract: Plant cell surface receptor-like kinases (RLKs) mediate the signals from microbe-associated molecular patterns (MAMPs) that induce immune responses. Lipopolysaccharide (LPS), the major constituent of the outer membrane of gram-negative bacteria, is a common MAMP perceived by animals and plants; however, the plant receptors/co-receptors are unknown except for LORE, a bulb-type lectin S-domain RLK (B-lectin SD1-RLK) in Arabidopsis. OsCERK1 is a multifunctional RLK in rice that contains lysin motifs (LysMs) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 52 publications
0
53
0
Order By: Relevance
“…Thus far, LORE homologs are confined to the Brassicaceae family, hence other undefined receptors are likely to be responsible for sensing LPS, or similar metabolites, in other plant families. In rice (Oryza sativa), OsCERK1, the receptor for chitin oligomers and peptidoglycan, also appears to mediate sensing of LPS from several bacterial species, including P. aeruginosa [56]. However, whether LPS is the specific ligand of this receptor has not been shown and requires further investigation.…”
Section: Animal and Plant Receptors Recognize Lps And Mount An Immunementioning
confidence: 99%
“…Thus far, LORE homologs are confined to the Brassicaceae family, hence other undefined receptors are likely to be responsible for sensing LPS, or similar metabolites, in other plant families. In rice (Oryza sativa), OsCERK1, the receptor for chitin oligomers and peptidoglycan, also appears to mediate sensing of LPS from several bacterial species, including P. aeruginosa [56]. However, whether LPS is the specific ligand of this receptor has not been shown and requires further investigation.…”
Section: Animal and Plant Receptors Recognize Lps And Mount An Immunementioning
confidence: 99%
“…Lastly, a recent study has reported OsCERK1, the chitin co-receptor, as an LPS receptor/co-receptor in rice, but not in A. thaliana [137]. This indicates a significant difference between LPS perception in rice and Arabidopsis.…”
Section: Lps Perceptionmentioning
confidence: 91%
“…Finally, OsCERK1 , but not AtCERK1 , was recently shown to be involved in perception of LPS, which is also not a GlcNAc-containing molecules ( Desaki et al, 2018 ).…”
Section: Phylogenetic Analysismentioning
confidence: 99%